Pengaruh Word of Mouth dan Kualitas Pelayanan terhadap Keputusan Mendaftar dengan Kualitas Prodi sebagai Variabel Moderating di Universitas Catur Insan Cendekia - Aditya Chandra (Jurnal Ekonomi Perusahaan, 2020)
The purpose of this study was to determine the effect of word of mouth and service quality on the decision of prospective students to register with campus quality as moderating. This research is motivated by the decreasing number of prospective students who come to Catur Insan Cendekia University in mid-2020, this indicates that the decision to register at Catur Insan Cendekia University has decreased. The primary data used in this study were taken using the accidental sampling method. The number of samples obtained was 106 respondents from the total population of prospective students at Catur Insan Cendekia University located in Cirebon, West Java. The respondents' answers were then analyzed using the SPSS program. The results of this study indicate that word of mouth has a significant effect on the decision to register, the quality of service has a significant effect on the decision to register. Word of mouth and service quality together have a significant effect on the decision to register. Product quality as a moderating variable is not able to strengthen word of mouth on the decision to register and product quality as a moderating variable is not able to strengthen the quality of service on the decision to register. Keywords: word of mouth; service quality; product quality; and the decision to register